Comparing the Influences on NO2 Changes in Terms of Inter-Annual and Seasonal Variations in Different Regions of China: Meteorological and Anthropogenic Contributions - Xuehui Bai; Yi Wang; Lu Gui; Minghui Tao; Mingyu Zeng (Remote Sensing)
NO2 primarily originates from natural and anthropogenic emissions. Given China’s vast territory and significant differences in topography and meteorological conditions, a detailed understanding of the impacts of weather and human emissions in different regions is essential. This study employs Kolmogorov–Zurbenko (KZ) filtering and stepwise multiple linear regression to isolate the effects of meteorological conditions on tropospheric NO2 vertical column densities. Long term trends indicate an overall decline, with anthropogenic contribution rates exceeding 90% in Shanghai, Changchun, Urumqi, Shijiazhuang, and Wuhan, where interannual variations are primarily driven by human emissions. In Guangzhou, the anthropogenic contribution rate exceeds 100%, highlighting the significant impact of human factors in this region, although meteorological conditions somewhat mitigate their effect on NO2. In Chengdu, meteorological factors also play a role. Seasonal variations display a U-shaped trend, and there are significant differences in the impact of meteorological factors on seasonal variations among different regions. Meteorological contribution rates in Changchun and Chengdu are below 36.90% and anthropogenic contributions exceed 63.10%. This indicates that changes in NO2 are less influenced by meteorological factors than by human activities, with human emissions dominating. In other regions, meteorological contributions are greater than those from human activities.